TRANSFORMASI LIVING HADIS DALAM PLATFORM DIGITAL: STUDI KASUS UNGKAPAN MASYÂ ALLÂH TABÂRAKALLAH DI KALANGAN SELEGBRAM BANJARMASIN - Hanafi, Hanafi (UIN ANTASARI BANJARMASIN, 2024)
This study aims to explore the transformation of living hadith in the context of digital platforms, with a particular focus on the use of the phrase